Base-promoted direct synthesis of functionalized N-arylindoles via the cascade reactions of allenic ketones with indoles. Issue 4 (10th January 2019) - Li, Shengxiao; Wu, Xin-Xing; Chen, Shufeng
Abstract : A convenient base-promoted cascade benzannulation reaction of allenic ketones with indole derivatives has been established. Abstract : A convenient Cs2 CO3 -promoted cascade benzannulation reaction of allenic ketones with indoles was achieved for the synthesis of functionalized N -arylindole derivatives under transition-metal-free conditions. A series of readily available starting materials can undergo the process successfully. It represents a practical method for the construction of N -arylindole scaffolds with high atom economy.